2019
DOI: 10.1109/tgcn.2018.2873783
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive-LPWAN: Towards Intelligent Wireless Services in Hybrid Low Power Wide Area Networks

Abstract: The relentless development of the Internet of Things (IoT) communication technologies and the gradual maturity of Artificial Intelligence (AI) have led to a powerful cognitive computing ability. Users can now access efficient and convenient smart services in smart-city, green-IoT and heterogeneous networks. AI has been applied in various areas, including the intelligent household, advanced health-care, automatic driving and emotional interactions. This paper focuses on current wireless-communication technologi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(52 citation statements)
references
References 30 publications
0
46
0
Order By: Relevance
“…In [22], the authors compare the performance of dynamic time division duplex with centralized and distributed resource allocation schemes in a dense IoT. The authors in [24] and [25] provide an overview on power consumption, security, spectrum resource management, and deployment of narrow band IoT and cognitive lowpower wide-area networks, respectively. In [26], we considered a system model in which there are periodic and critical messages coexisting in an IoT system and proposed a learning framework that enables the IoT devices to autonomously allocate the limited communication resources for a highly reliable transmission of the critical messages.…”
Section: A Existing Workmentioning
confidence: 99%
“…In [22], the authors compare the performance of dynamic time division duplex with centralized and distributed resource allocation schemes in a dense IoT. The authors in [24] and [25] provide an overview on power consumption, security, spectrum resource management, and deployment of narrow band IoT and cognitive lowpower wide-area networks, respectively. In [26], we considered a system model in which there are periodic and critical messages coexisting in an IoT system and proposed a learning framework that enables the IoT devices to autonomously allocate the limited communication resources for a highly reliable transmission of the critical messages.…”
Section: A Existing Workmentioning
confidence: 99%
“…(6) where (7) The parameter P BS,s represents the transmit power of serving base station BS and G j,BS,s represents the channel gain between user j and base station BS on subcarrier s. Similarly the parameter P BS',s represents the transmit power of neighboring base station BS' and G j,BS',s represents the channel gain between user j and neighboring base station BS' on subcarrier s. The N 0 is white noise power spectral density and ∆f represent subcarrier spacing. The channel gain G is represented by the path loss (PL) model based on the urban path-loss and given as (8).…”
Section: B Throughput Measurementmentioning
confidence: 99%
“…7]. Different wireless communication techniques such as LTE, NB-IoT, EC-GSM, Lora, Sigfox are compared using parameters coverage, Spectrum, Bandwidth, Data rate, Battery life in [8]. The software defined radio technology for LTE transmit diversity is explained using USRP N210 and study the BER performance [9].…”
Section: Introductionmentioning
confidence: 99%
“…They extended their work in another article toward improving LPWAN communication over white spaces . Similarly, Chen et al introduced cognitive‐LPWAN (C‐LPWAN) based on an artificial intelligence (AI)‐enabled cognitive engine . They suggested that C‐LPWAN performs better than some known LPWAN technologies such as LoRa (Long Range), NB‐IoT, and LTE‐M in terms of its delay reduction and minimal energy consumption rates.…”
Section: Introductionmentioning
confidence: 99%